The degree of mastering critical reading skills for six grade Students: A case Study in lattakia schools - Ammar, Sam; Asaad , Dalia (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This paper aims to determine the level of six grade students in critical reading skills. Thus, it shows the differences in their performance in the test of critical reading skills in respect to gender variable. To achieve this goal, the researcher designed a list of critical reading skills. Five of these skills included (17) behavioural indicators. With all these ideas in mind, the researcher applied a test to measure the degree of mastering these skills among students. The researcher adapted qualitative methodology. The study sample was (130) six grade male and female students in Lattakia province. The researcher concluded the following points: 1. Students showed incompetency in their use of critical reading skills as their average level was 45.78 with each skill measured by itself. 2. There were no statistical differences among students’ scores in the test of critical reading skills that could be attributed to gender variable.